2012
DOI: 10.3144/expresspolymlett.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of car shredder polymer waste with Raman mapping and chemometrics

Abstract: A novel evaluation method was developed for Raman microscopic quantitative characterization of polymer waste. Car shredder polymer waste was divided into different density fractions by magnetic density separation (MDS) technique, and each fraction was investigated by Raman mapping, which is capable of detecting the components being present even in low concentration. The only method available for evaluation of the mapping results was earlier to assign each pixel to a component visually and to count the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The vibrational techniques are widely used for exploration of quantitative information in many fields (e.g. in food industry, plastic industry or art) . In the pharmaceutical industry especially the chemical imaging (CI) is gaining interest currently due to its versatile applicability in pharmaceutical processes .…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational techniques are widely used for exploration of quantitative information in many fields (e.g. in food industry, plastic industry or art) . In the pharmaceutical industry especially the chemical imaging (CI) is gaining interest currently due to its versatile applicability in pharmaceutical processes .…”
Section: Introductionmentioning
confidence: 99%
“…After a comprehensive component analysis (Fourier transform infrared spectroscopy -FTIR, Raman, thermogravimetry -TG, differential scanning calorimetry -DSC) [17], it was found that below the density of 900 kg/m 3 the main polymer component is polypropylene (>#78 %), melt flow rate (MFR) (190°C, 2.16 kg) 2.14 g/10 min and its inorganic filler residue content (determined by heating under mass loss calorimeter with heating wire of 900°C, which means approx. 650°C on the surface of the samples) is lower than 0.75 mass%, containing mainly talc, calcium-carbonate and short glass fibre.…”
Section: Methodsmentioning
confidence: 99%
“…The vibrational spectroscopy such as Raman or NIR is potentially useful to provide qualitative [2] and quantitative [3][4][5][6] information about the studied substances. In addition, the application of imaging procedure allows us to obtain a number of local, pixel-like data in lateral or even vertical directions.…”
Section: Introductionmentioning
confidence: 99%